Extent of arsenic contamination and its impact on the food chain and human health in the eastern Ganges Basin: a review - Natarajan, Rajmohan; Prathapar, Sanmugam A. (International Water Management Institute, 2014)
Exposure to arsenic and the use of arsenic-contaminated groundwater in agriculture causes serious health issues. Complete or partial contamination of groundwater is reported worldwide, especially in the Eastern Gangetic Basin (EGB). This study aims to create an overall assessment of arsenic contamination in the EGB based on existing literature, demarcate the extent of the affected area, highlight the impacts on the food chain and human health, and hopes the research will help in the better planning and management of groundwater. Although several studies have evaluated arsenic contamination of groundwater in the EGB, (a) there is no proper long-term monitoring being done in affected areas; (b) there is a debate to identify the exact source and transport processes of arsenic occurrence in this region; (c) there is no comprehensive method to estimate the level of arsenic contamination in soil, water and the food chain; and (d) Arsenic contamination in Bihar and Nepal is not evaluated systematically, especially arsenic accumulation in the food chain and human health issues. Data scarcity and accessibility are the major challenges in this region. Thus, this review recommends systematic monitoring and analysis of arsenic contamination in groundwater, soils and food across the EGB.